Cocoa: Production and processing - Adabe, K. Edoh; Ngo-Samnick, E. Lionelle (Technical Centre for Agricultural and Rural Cooperation, 2014)
A highly nutritious crop, cocoa constitutes a significant source of income for small-scale producers. Attractively presented, with full-colour illustrations, tables and step-by-step guides, the text clearly sets out the procedure to start growing cocoa. In addition to recommending a technical schedule for the production of cocoa plants, the guide stresses the importance of phytosanitary protection and post-harvest operations. Useful advice and economic information on the sector is also given in later chapters.